Hygroscopicity of Organic Aerosols and Their Contributions to CCN Concentrations Over a Midlatitude Forest in Japan. Issue 17 (14th September 2018) - Deng, Yange; Kagami, Sara; Ogawa, Shuhei; Kawana, Kaori; Nakayama, Tomoki; Kubodera, Ryo; Adachi, Kouji; Hussein, Tareq; Miyazaki, Yuzo; Mochida, Michihiro
Abstract: The formation of biogenic secondary organic aerosols (BSOAs) in forest environments is potentially important to cloud formation via changes of the cloud condensation nuclei (CCN) activity of aerosols. In this study, the CCN activation of submicrometer aerosols and their chemical compositions and size distributions were measured at a midlatitude forest site in Japan during the summer of 2014 to assess the hygroscopicity of the organic aerosols and their contributions to the local CCN concentrations. The mean number concentrations of the condensation nuclei and CCN at supersaturation (SS) conditions of 0.11–0.80% were 1, 238 and 166–740 cm −3, respectively. Organic aerosols and sulfate dominated the submicrometer aerosol mass concentrations. The particle hygroscopicity increased with increases in particle diameters. The hygroscopicity parameter for the organics, κ org, was positively correlated with the atomic O to C ratio. The product of κ org and the volume fraction of OA was 0.12, accounting for 38% of the water uptake by aerosol particles. The hygroscopicity parameter of the locally formed fresh BSOA was estimated to be 0.09. The contribution of OA to the CCN number concentration, which was assessed by subtracting the CCN concentration of the hypothetical inorganic aerosols from that of the ambient aerosols, was 50–182 cm −3 for the SS range of 0.11–0.80%. The increase of the CCN number concentrations per 1‐μg/m 3 increase of the BSOA was 23–299 cm −3 at 0.11–0.80% SS. The contribution of the BSOA to the CCN number concentration can be enhanced by new particle formation. Plain Language Summary: Some of the particles suspended in the atmosphere can absorb water vapors around them and act as nuclei to form cloud droplets. These particles are called cloud condensation nuclei (CCN), the quantification of which is important for climate forcing prediction. The ability of a particle to absorb water is referred to as hygroscopicity, which is governed by the chemical composition. Volatile organic vapors emitted by vegetation (i.e., biogenic volatile organic compound) after chemical reactions in the atmosphere can either condense onto existing particles or participate in the formation of new particles and thus change the aerosol chemical composition. The aerosol component originated from biogenic volatile organic compounds, named biogenic secondary organic aerosol (BSOA), is an important constituent of CCN on a global scale. However, the hygroscopicity of BSOA and its contribution to CCN are not understood well. We performed measurements of the hygroscopicity and chemical composition of aerosol particles in a forest in Japan. Based on the observation, we calculated the hygroscopicity of the BSOA formed in the forest and quantified the contribution of the BSOA to the CCN number concentrations. An enhancement of the contribution of BSOA to the CCN number concentrations by new particle formation is suggested, which is an important subject of future studies. Key Points: Organics contributed to, on average, 38% of the aerosol water uptake The hygroscopicity parameter of locally formed fresh BSOA was estimated to be 0.09 Per 1‐μg/m 3 increase of BSOA, the CCN concentration increased 23–299 cm −3 at 0.1–0.8% SS